Saponin-Rich Plant Premixture Supplementation Is as Efficient as Ionophore Monensin Supplementation Under Experimental Eimeria spp Challenge in Broiler Chicken - Benarbia, Mohammed el Amine; Gaignon, Pierre; Manoli, Claire; Chicoteau, Pierre (Frontiers in Veterinary Science, 2022)
For decades avian coccidiosis prevention was based on the use of synthetic coccidiostats. However, their intensive use led to the development of resistance phenomena. In addition, societal demand is increasing for antibiotic-free animal products. Thus, there is a need for a natural and efficient solution for coccidiosis management. Saponin-rich plants like Yucca schidigera and Trigonella foenum-graecum are promising tools for coccidiosis management. This study assessed the effects of supplementing broiler chickens with a commercial blend of these two plants (NorponinXO2) under an experimental Eimeria challenge and compared their effects to monensin supplementation. 3 trials were performed. For each trial, chickens were divided into 4 groups, untreated uninfested control (UUC), infested untreated control (IUC), infested supplemented with 120 ppm of Monensin in feed (PM), infested supplemented with 250 ppm of Norponin XO2 in the feed (PX). Chickens were raised in cages; experimental infestation was performed on d14. On d21, intestinal lesions (ILs) scores and growth performances were recorded. A statistical study was carried out on each trial as well as data from the 3 trials. Experimental infestation reduced in a significant way final body weight in IUC broilers compared to UUC broilers. This loss was numerically compensated by PM and PX treatment. As expected, intestinal lesions were almost absent in the UUC group, however, broilers from the IUC group showed a higher intestinal lesion occurrence. Supplementations with Monensin and NPXO were able to reduce intestinal lesions occurrence. These results suggest that NPXO supplementation is as efficient as Monensin in managing coccidiosis.